A DEVELOPMENT RESEARCH OF LISTENING INSTRUCTIONAL MATERIALS FOR BUSINESS ADMINISTRATION STUDY PROGRAM STUDENTS - Angelina, Yovita; Sutapa Y, Y. Gatot; ., Ikhsanudin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract : This development research was conducted to construct a model of authentic listening instructional materials for Business Administration study program students at Politeknik Negeri Pontianak (POLNEP). The procedure of the study adapted Dick, Carey, and Carey Approach model (2009). The development was conducted based on the result of identifying instructional goals that showed the unavailability of practice and theory on listening at Polnep. The instruments consisted of questionnaires, an interview guide, and field notes. The final product had been obtained by the processes of validation and try-out. Some revisions were on task time allocation, instructions in exercises, some words choices, and reflection session. In this research, the three subject matter experts (SME) who evaluated the product were the experts in the field of the English Teaching; Dra. Juliana Sujadi, M.Ed., the English Teaching Methodology and Wording; DR. Istiqamah, MA., and the English Teaching Materials; DR. Refnaldi, M.Litt. The final product had been able to fulfil the Listening materials for semester one and three students in classroom usage as well as for self directed learning. The materials had also met both the students? level of diffiiculty and time allowance. Keywords: Unavailability, Instructional, Seft-Directed, Product, Try-out. Abstrak : Penelitian pengembangan ini bertujuan untuk merancang sebuah model pengajaran untuk mata kuliah Listening di Politeknik Negeri Pontianak (POLNEP) jurusan Administrasi Bisnis. Adapun prosedur penelitiannya menerapkan model Dick, Carey and Carey (2009). Pengembangan materi didasarkan pada analisa terhadap ketidak tersediaan materi untuk Listening di POLNEP. Instrumen pada analisa kebutuhan mencakup wawancara, kuesioner dan catatan penelitian. Produk akhir telah dicapai melalui proses validasi dan try out. Perbaikan dilakukan pada alokasi waktu pengerjaan tugas, instruksi pada latihan, beberapa pilihan kata, dan sesi tambahan. Ketiga ahli yang melakukan validasi, yaitu: para ahli di bidang: (1) pengajaran dalam bahasa Inggris; Dra. Juliana Sujadi, M.Ed., (2) pemilihan kata dan metodologi dalam pengajaran bahasa Inggris; DR. Istiqamah, M.A, dan (3) bahan ajar bahasa Inggris; DR.Refnaldi,M. Litt. Produk akhir dapat memenuhi bahan ajar Listening untuk mahasiswa semester pertama dan ketiga serta dapat menjadi bahan belajar mandiri. Produk akhir juga memenuhi kriteria tingkat kesulitan mahasiswa dan ketersediaan waktu dalam satuan kredit. Kata Kunci : Ketidaktersediaan, Bahan ajar, Belajar mandiri, Hasil, Try-out